Inclusion Properties for Certain Classes of Meromorphic Functions Associated with a Family of Linear Operators. (4th June 2009) - Cho, Nak Eun
Abstract : The purpose of the present paper is to investigate some inclusion properties of certain classes of meromorphic functions associated with a family of linear operators, which are defined by means of the Hadamard product (or convolution). Some invariant properties under convolution are also considered for the classes presented here. The results presented here include several previous known results as their special cases.